Higher Education Waqf Governance at Malaysian Public Universities: An Exploratory Study - Yaacob, Hisham; Syed Yusuf, Sharifah Nurzehan; Mohamed, Intan Salwani (Journal of Islamic, Social, Economics and Development, 2025)
The reduction in government funding for public education in Malaysia has led public universities to find alternative resources. Therefore, waqf (Islamic endowment) is proposed as one of the possible solutions. Waqf is interesting because the accountability system is different as it has triple accountability: upward accountability to God, lateral accountability, and downward accountability to beneficiaries and donors as well as other stakeholders. The objective of this study is to examine the higher education waqf governance practices at Malaysian public universities. This study is interpretive and applies the qualitative approach of grounded theory methods. A total of five interviews were completed for the exploratory study. The study used the purposive and theoretical sampling methods to select the sample. The study found the Malaysian Ministry of Higher Education prescribes three governance models and all three universities in the sample adopted the third model of shared governance with the State Islamic Religious Council. One important point voiced by a few respondents is that some improvements are needed in the governance structure to enhance the higher education waqf accountability and sustainability. The study is among the pioneer to examine the higher education waqf governance at Malaysian public universities using the grounded theory methods to understand the governance practices.